2017
DOI: 10.17159/2519-0105/2017/v72no5a1
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Financially Independent Retirement

Abstract: Objectives: The study investigated whether dentists in South Africa are actively planning for retirement and if they are confident about being able to retire as financially independent.Methods: An anonymous online questionnaire was used to collect data from private dental practitioners who were members of the South African Dental Association. Stata release 11 was used for descriptive statistical analysis.results: The majority of the respondents (71%) were male and 42% of respondents were older than 50 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…The use of online surveys to elicit the views of members of the SADA database has been previously used in several studies. [20][21][22] The findings of the present study may, therefore, be considered valid for the target group identified, however, it is important to note that the findings may not be representative of the views of all registered dentists in South Africa -a number Bhayat and Chikte estimated to be approximately 6 125 in 2015. [17] Responses, however, were obtained across a wide distribution of ages and a large geographical area, with approximately equal representation of both males and females.…”
Section: Discussionmentioning
confidence: 91%
“…The use of online surveys to elicit the views of members of the SADA database has been previously used in several studies. [20][21][22] The findings of the present study may, therefore, be considered valid for the target group identified, however, it is important to note that the findings may not be representative of the views of all registered dentists in South Africa -a number Bhayat and Chikte estimated to be approximately 6 125 in 2015. [17] Responses, however, were obtained across a wide distribution of ages and a large geographical area, with approximately equal representation of both males and females.…”
Section: Discussionmentioning
confidence: 91%
“…Financial security may be reflective of a regular retirement income (Adzawla et al, 2015;Dovie, 2018), whether sufficient or otherwise. Research (e.g., Snyman et al, 2017) has shown that finances are the strongest single predictor of the decision to retire and that people are more likely to leave the workforce if they can financially afford to retire than if they cannot.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of sustaining income remains an important factor that influences the choice of retirement age by workers who wish to retire voluntarily. The strongest motive for the decision to exit the workforce is hinged is finances; an early exit is likely if workers have funds to cater for their retirement period, (Snyman, van der Berg-Cloete & White, 2017). Physical or mental health and occupational stress are other motives for retirement.…”
Section: ~ 193 ~mentioning
confidence: 99%